Pliocene animal trackways at laetoli: research and conservation potential - Musiba, Charles M.; Mabula, Audax; Selvaggio, Marie M.; Magori, Cassian C. (Ichnos-an International Journal for Plant and Animal Traces, 2008)
Laetoli, a paleoanthropological site in Northern Tanzania, is perhaps best known for its famous fossil hominid footprints that were discovered by Mary Leakey and her co-workers in 1978. The site not only preserves the hominid footprints but also trackways, which provide a snapshot of Pliocene faunal communities from East Africa and their inferred environments. Unlike the hominid footprints at site G, which have received tremendous attention, the animal trackways, especially at Localities 7, 8 and 10 have been neglected and are fast disappearing. In this paper, we discuss animal tracks at a newly discovered exposure and provide preliminary data on the tracks at this exposure and other sites. We also discuss the importance of the animal trackways as ecological indicators, which we have investigated as part of ongoing research and conservation efforts initiated by the Tanzania Field School in Paleoanthropology and the Associated Colleges of the Midwest (ACM) Tanzania Semester Abroad programs.
Keywords: Africa; Animal trackway conservation; Animal trackways; Animalia; East Africa; Hominidae; Laetoli; Paleoecology; Pliocene; Sub-Saharan Africa; Tanzania; anthropology; conference proceeding; dept.ant; footprint; hominid; paleoecology; trackway

Landscape-scale variation in hominin tool use: Evidence from the Developed Oldowan - Braun, David R.; Rogers, Michael J.; Harris, John W. K.; Walker, Steven J. (Journal of Human Evolution, 2008)
The relationship between artifact manufacture, use, and discard in the Developed Oldowan is complex. Here we use digital-image-analysis techniques to investigate the intensity of reduction in single-platform cores of the Developed Oldowan of the Okote Member, Koobi Fora Formation. Data suggest that this method provides a more accurate measure of reduction intensity than previous applications of a unifacial-scraper model. Assemblages of single-platform cores excavated from extensive lateral exposures of the Okote Member provide insights into the relationship between raw-material availability and discard patterns. Variation in reduction intensity suggests that tools are not always discarded in patterns that would be predicted by the availability of raw material. Further, it appears that hominin transport decisions involved an assessment of the potential use-life of certain forms. Many aspects of Developed Oldowan technology conform to previously developed models of curated technologies. (C) 2008 Elsevier Ltd. All rights reserved
Keywords: Curation; Hominin behavior; Landscape archaeology; Oldowan; Pleistocene; Stone Age; Stone tools; dept.ant; hominid; image analysis; peer-reviewed; tool use

Prehistoric trepanation in the Cuzco region of Peru: A view into an ancient Andean practice - Andrushko, Valerie A.; Verano, John W. (American Journal of Physical Anthropology, 2008)
In this study, patterns of prehistoric trepanation in the southern highlands of Peru were examined through an analysis of 11 Cuzco-region burial sites. Trepanations were found in 66 individuals, with several individuals exhibiting more than one trepanation, for a total of 109 perforations observed. The predominant methods used were circular cutting and scraping-methods that proved highly successful with an overall 83% survival rate and little ensuing infection. Survival rates showed a significant increase over time, apparently reflecting improvements in trepanation technique through experimentation and practical experience. Practitioners avoided certain areas of the cranium and employed methods that reduced the likelihood of damage to the cerebral meninges and venous sinuses. In many cases, trepanation as a medical treatment appears to have been prompted by cranial trauma, a finding that corroborates other studies pointing to cranial trauma as a primary motivation for the surgical procedure.
Keywords: *Skull/su [Surgery]; *Trephining/hi [History]; Cranial trauma; Culture; Cuzco; History, Ancient; Humans; Inca; Paleopathology; Peru; Skull; Skull Fractures; Skull Fractures/hi [History]; Skull Fractures/su [Surgery]; Skull/pa [Pathology]; Treatment Outcome; Trepanation; Trephining; Trephining/is [Instrumentation]; Trephining/mt [Methods]; Wounds and Injuries; Wounds and Injuries/hi [History]; Wounds and Injuries/su [Surgery]; adult; aged; article; controlled study; dept.ant; experimentation; female; head injury; human; human tissue; male; meninx; peer-reviewed; prehistoric period; school child; sinus venosus; skull; surgical technique; survival rate; trepanation

New evidence for hominin carcass processing strategies at 1.5 Ma, Koobi Fora, Kenya - Pobiner, Briana L.; Rogers, Michael J.; Monahan, Christopher M.; Harris, John W. K. (Journal of Human Evolution, 2008)
Reconstruction of early Pleistocene hominin carcass acquisition and processing behaviors are necessarily based at least in part on butchered fossil bones. This paper provides zooarchaeological and taphonomic analyses and behavioral interpretations of three similar to 1.5 million-year-old archaeofaunas from areas 1A and 103 in the Okote Member of the Koobi Fora Formation, northern Kenya: FwJj14A, FwJj14B, and GaJi14. These sites are all located in similar paleoenvironmental contexts, near shallow water with swampy, seasonally flooded areas, and some evidence for more wooded or gallery forest settings. Both individual specimen- and assemblage-level analyses of butchery-marked bones indicate that the hominins appear to have practiced similar butchery strategies at all of these sites, with butchery (defleshing, disarticulation, and marrow extraction) of both high- and low-ranked skeletal elements with no apparent preference for prey size, skeletal region, limb class, or limb portion. Only four tooth-marked specimens, including one likely crocodile-tooth-marked bone, are preserved in all three archaeofaunas. A paucity of limb epiphyses suggests that bone-crunching hyenids may have deleted these portions subsequent to hominin butchery. Strangely, there are no stone tools preserved with the 292 cut-marked and 27 percussion-marked faunal specimens (out of a total of 6,039 specimens), suggesting that raw material availability may have conditioned hominin lithic discard patterns at these locales. These assemblages increase our knowledge of the dietary behavior and ecology of Homo erectus, and provide support for variability in early Pleistocene hominin carcass foraging patterns. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Africa; Alligator; Bone modification; Butchery; Carnivory; Cut mark; Early Stone Age; East Africa; Homo erectus; Kenya; Koobi Fora; Oldowan; Percussion mark; Pleistocene; Rift Valley; Sub-Saharan Africa; Turkana; bone; carnivory; dept.ant; hominid; paleoecology; peer-reviewed; taphonomy

Cranioplasty in ancient Peru: a critical review of the evidence, and a unique case from the Cuzco area - Verano, John W; Andrushko, V A (International Journal of Osteoarchaeology, 2008)
Cranioplasty is a well-known procedure in modern neurosurgery. Although some authors have claimed it was also performed by prehistoric trepanners in various parts of the world, there is little hard evidence to support this. Here we review various claims of cranioplasty in Peru, where trepanation was widely practised in Prehispanic times. We find little support for assertions that cranioplasty was common. One recently discovered burial from the Cuzco region, however, provides the first documented case of the reinsertion of a bone plug into a trepanation opening. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: Cranioplasty; Peru; Trepanation; dept.ant; peer-reviewed